PENGGUNAAN TEKNOLOGI DALAM PENDIDIKAN TANTANGAN GURU PADA ABAD 21 - Siswanti, Linda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
One of the challenges of teachers in the 21stcentury is the use of technology in education. In general, experts argue that multiple-faced technology. On the one hand, technology provides many conveniences and benefits, so there are teachers who rely on the use of technology in education. However, on the other hand, technology can also have a negative impact on education. The use of scaffolding in the form of technology can eliminate the essence of education. Therefore, the use of technology as an educational support must be accompanied by an awareness to continue to accommodate and maintain that essence. The essence of education is not only about transfers knowledge, but also gives exemplary, inculcates good values, fosters character, fosters potential